News coverage of foreign sex workers in Malaysia: a critical analysis - Puspalata C Suppiah,; Surinderpal Kaur,; Nalini Arumugam,; Alice Shanthi, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The growing concern over the influx of foreign women in Malaysia as sex workers, has continually gained the attention of the local media particularly the mainstream newspapers. The media, despite playing an instrumental role in bringing about social transformation, has the ability to portray the foreign women in a positive way or to discriminate against them. This study, based on qualitative analysis, represents an attempt to study a social problem particularly in the way that foreign women in sex work have been represented in Malaysia by the mainstream English-language newspapers. The analytical tools of the discourse-historical approach (DHA) are employed in the analysis of the news articles. In particular, the argumentation strategy in the DHA demonstrates that a number of topoi (i.e., the topoi of control, number, threat, and victimisation) have been employed to represent foreign sex workers in the media. Investigation of the newspaper extracts from New Straits Times and The Star generally revealed that the media have portrayed foreign women in sex work in the offender orientation frame more so than as victims. Furthermore, foreign sex workers are also positioned negatively because of their illegal migrant status, making them doubly discriminated against. Such representations directly impact the women’s lives, leading to further discrimination on the basis of their trade and illegal migrant status, denying them a voice and depriving them of their legal rights. The paper concludes by discussing the contributions of the research and emphasises the need for social justice for these marginalised women.